Avian Influenza Awareness and Profitability of Poultry Egg Production in Oyo State, Nigeria - Ajetomobi, J.O.; Adepoju, A.A. (International Journal of Poultry Science, 2010)
This study examines the effects of customers’ awareness of avian influenza on poultry egg production enterprise in Lagelu local government area of Oyo State. Primary data were collected from forty-eight poultry farms in the study area using multistage sampling technique. Data collected were analyzed using descriptive statistics, budgetary analysis and multiple regression analysis. The result showed that poultry egg production in the study area is dominated by male (75%) with about 50% of the farmers in their productive age i.e. 21-40 years. Majority of the farmers had formal education (87.5%). The outbreak of the news accounted for about 85% reduction in the farmers’ gross margin per bird. The most effective home grown strategy to restore consumers’ confidence was routine hygiene management. The literacy level of farmers afford the farmers the opportunity of timely information about the disease and possible general management practices.